On earnings and cash flows as predictors of future cash flows - Ball, Ray; Nikolaev, Valeri V. (Journal of Accounting and Economics, 2022)
Do accruals-based earnings provide better information about future operating cash flows than do operating cash flows themselves, as predicted by the Financial Accounting Standards Board's conceptual framework (FASB, 1978)? While this is a foundational issue in accounting, because it addresses the information added by accrual accounting methods, testing it remains unsettled. We show that when comparing the predictive ability of operating cash flows with that of an equivalent earnings measure calculated on an accrual basis, earnings outperform operating cash flows. The result becomes more pronounced when allowance is made for cross-sectional differences in the relation between firms' earnings and future cash flows. In fact, even “bottom line” earnings then have similar explanatory power as operating cash flows.